PENGGUNAAN MEDIA VIDEO PEMBELAJARAN BERBASISI HP ANDROID TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK KELOMPOK B DI TK PGRI MELUR - Emawati Emawati; Elnawati Elnawati; Redi Awal Maulana (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the effect of using Android-based video learning media on the ability to recognize number concepts in group B children at PGRI Melur Kindergarten. The ability to recognize number concepts is an important aspect in the cognitive development of early childhood, which is the basis for understanding mathematics at the next level. However, initial observations showed that many children still have difficulty in recognizing numbers, counting objects, and understanding the concept of numbers as a whole. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of two cycles. Each cycle involves the planning, implementation, observation, and reflection stages. The subjects of the study were 15 group B children at PGRI Melur Kindergarten aged 5-6 years. Data were collected through observation, documentation, and interviews, which were then analyzed using quantitative and qualitative descriptive methods. The results of the study showed that the use of Android-based video media significantly improved children's ability to recognize number concepts. In the pre-cycle, 53% of children were in the Not Developing (BB) category, and only 7% reached the Very Well Developing (BSB) category. After cycle II, there were no more children in the BB category, with 47% of children reaching the Developing According to Expectations (BSH) category and 40% reaching the BSB category. This increase shows that Android-based video media is effective in helping children understand number concepts better through a visual and interactive approach. Interesting and interactive video media has been proven to increase children's interest in learning, involvement, and understanding of number concepts. Thus, the use of Android-based learning video media can be used as an effective strategy in early childhood learning, especially in improving understanding of number concepts.